Fostering Harmony in Diversity: A Bibliometric Analysis of Research Articles on Interfaith Tolerance - Fitriani, Ely; Akbari, M. Yudo Agresi; Fuad, Ah. Zakki; Syaifudin, Mokhamad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze the distribution of research articles with the theme of tolerance between religious communities in the Scopus database. Scopus journals are known to have high quality standards so it is certain that the articles collected in them are of good quality. Furthermore, the VOSviewer application is used as an analytical tool in research using a bibliometric approach. The results of the research focused on finding and analyzing topics that have a connection with interfaith tolerance. Data on the number of documents/articles with the theme of tolerance between religious communities contained in the Scopus database with the period 1993 - 2024 are 33 documents. This topic is an interesting thing to continue to be researched by further researchers, this is due to the graphical increase in this theme every year which indicates that this topic is increasingly in demand by researchers, this will certainly have a huge impact in fostering harmony in diversity.